Effects of Si concentrations on microstructure and mechanical properties of as-cast CoCrMo alloys - P. Tunthawiroon; A. Chiba (My University, 2019)
Abstract This research investigates the effects of different Si concentrations on the microstructure and mechanical properties of Co–Cr–Mo–xSi alloys. The Si concentration (x) was 0.1, 0.5, 1.0, 3.0 and 5.0 wt%. The mechanical properties of the experimental heat-treated Co–Cr–Mo–xSi alloys was determined by hardness and tensile tests. The microstructure was analyzed using SEM. The microstructure analysis revealed that Si concentration played a role in the formation of the intermetallic phase of Co–Cr–Mo–xSi alloys. The presence of the intermetallic phase significantly decreased the ductility of the experimental alloys. However, the hardness was improved and was increased directly proportional to the fraction of the intermetallic phase precipitating in the Co–Cr–Mo–xSi alloys.
Keywords: Ductility (Earth science); Advanced materials and composites